2022
DOI: 10.3390/plants11121527
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of the Interaction of Maize Inducer and Donor Backgrounds on Haploid Induction Rates

Abstract: Doubled haploid technology is a feasible, fast, and cost-efficient way of producing completely homozygous lines in maize. Many factors contribute to the success of this system including the haploid induction rate (HIR) of inducer lines, the inducibility of donor background, and environmental conditions. Sixteen inducer lines were tested on eight different genetic backgrounds of five categories in different environments for the HIR to determine possible interaction specificity. The HIR was assessed using the R1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…This hybrid was chosen as a donor because it possesses good inducibility and allows clear expression of the R1-nj marker. Inducibility is the ability of the donor parent to generate haploid seeds, and multiple studies indicated that the source germplasm impacts HIR ( Randolph, 1940 ; Chase, 1952 ; Lashermes and Beckert, 1988 ; Eder and Chalyk, 2002 ; De La Fuente et al., 2018 ; Nair et al., 2020 ; Ren et al., 2022 ; Trentin et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…This hybrid was chosen as a donor because it possesses good inducibility and allows clear expression of the R1-nj marker. Inducibility is the ability of the donor parent to generate haploid seeds, and multiple studies indicated that the source germplasm impacts HIR ( Randolph, 1940 ; Chase, 1952 ; Lashermes and Beckert, 1988 ; Eder and Chalyk, 2002 ; De La Fuente et al., 2018 ; Nair et al., 2020 ; Ren et al., 2022 ; Trentin et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…The selection of haploid kernels based on the R1-nj can be limited by factors such as (1) the presence of dominant C1 anthocyanin inhibitor genes (c1-I, c2-Idf, in1-D) (Khulbe et al, 2022), (2) an occurrence of an outcross which is a result of pollen contamination from an outside source instead of an inducer line, (3) physical seed 4 Emerson, 1921;Briggs, 1966;Coe et al, 1988;Chaikam et al, 2016;Vanous et al, 2017;Trentin et al, 2020. 5 Chandler et al, 1989Coe, 1994;Chaikam et al, 2016. properties, (4) donor germplasm with natural anthocyanin expression in the aleurone layer, and (5) environmental factors (Prigge et al, 2011;Trentin et al, 2022). The presence of dominant anthocyanin inhibitor genes such as C1-I, C2-ldf, and in-1D (Coe et al, 1988;Stinard and Sachs, 2002) suppress R1-nj expression.…”
Section: H Vs D Determination Advantages Limitationsmentioning
confidence: 99%
“…Physical seed properties such as seed shape, seed moisture content, and the presence of air pockets underneath the pericarp (Rotarenco et al, 2010;Prigge et al, 2011) can alter R1-nj expression. The scutellum of the embryo was more visible in flat than in round seeds, meaning that R1-nj expression was more intense in dent maize than in flint maize (Eder and Chalyk, 2002;Trentin et al, 2022;Thawarorit et al, 2023). The air pockets are triggered when the seed moisture content drops to low levels due to delaying harvest time and extending the duration of seed drying.…”
Section: H Vs D Determination Advantages Limitationsmentioning
confidence: 99%
“…This approach consists of four steps: haploid induction, haploid identification, chromosome doubling, and seed production from double haploid lines (Chaikam et al 2019). Despite the advantages of using double haploids in common corn, there are some studies on induction rates in LF Souza et al supersweet corn (Sekiya et al 2020, Trentin et al 2022, but few reports exist on their effective use to generate inbred lines (Khulbe et al 2020).…”
Section: Introductionmentioning
confidence: 99%